Identifying the border of the western Kurdistan region - Sulaiman Abdulla Ismail; Imad Abdullah Huseen Rasul (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The Western Region of Kurdistan is the geographical area that extends and complements the north and south of Kurdistan. There is no geographical and natural separation that separates it from the rest of Kurdistan. The area of the Western Kurdistan Region (33150 km2) ، according to the administrative division of the Syrian state، the territory of the western region is located within four governorates of Syria، namely The Governorate of Hasaka، Raqqa، Aleppo، Idlib، about 18% of the total territory of the Syrian state، and about 4.8% of the territory of Kurdistan It makes up big.